POTENSI EKSTRAK ETANOL BIJI JINTEN HITAM (NIGELLA SATIVA L.) MENURUNKAN KADAR GLUKOSA DARAH PADA TIKUS PUTIH (Rattus norvegicus) JANTAN KONDISI HIPERGLIKEMIK. - Ivan Charles Seran; Agustinus Alfred (MEDFARM: Jurnal Farmasi dan Kesehatan, 2022)
Diabetes mellitus is a disease characterized by elevated blood sugar levels, one of which is often exposed to free radicals. The purpose of this study was to determine the effects of hypoglycemia and ethanol extract on black cumin seeds. This may affect the reduction in blood glucose levels and the increase in weight gain and food intake induced by alloxan in laboratory rats. This study is an experimental laboratory study using only a post-test class design. Subjects of this study were his 30 male Wistar rats who were adjusted for his type 2 diabetes using alloxan induction. The rats he divided into six groups. group II negative control alloxan 150 mg/kg body weight; group III positive control glibenclamide 0.45 mg/kg body weight; kg body weight, Group V black cumin seed ethanol extract dosage 200 mg/kg body weight. The results showed that black seed ethanol extract at doses of 100, 200, and 400 mg/kg body weight reduced blood glucose levels and increased body weight and food intake in experimental rats. The most effective dose is 400 mg/kg body weight.